Limits to government debt sustainability in middle-income countries - Fournier, Jean-Marc (OECD Economics Department Working Papers, 2018)
This paper investigates the effect of structural characteristics on debt limits of middle income countries. Two equations relate the probability of default to the interest rate. First, the probability of default is estimated with a logit model. Second, the assumption of non-arbitrage opportunity on the sovereign bond market relates the interest rate, the probability of default and the recovery rate. This model leads to three situations: a single and stable solution at low debt, multiple equilibria with stable and unstable solutions at intermediate debt, and a single solution with dissuasively high risk-premium beyond a debt threshold: this defines the debt limit. It reflects the empirical evidence on default determinants: it increases with perceived government effectiveness, the export to GDP ratio and the expected recovery rate and decreases with the commodity export to GDP ratio, the size of growth shocks, the share of defaults in neighbouring countries, the risk-free rate and investors' risk aversion. Debt limits are highly sensitive to the expected recovery rate, reflecting the importance of credibility. The multiple equilibria case illustrates the risk of self-fulfilling crises: interest rate shocks can trigger the default below the debt limit